POLITICIANS BACK TO THEIR OLD TAXING WAYS (Tufts Archival Research Center, 2007)
Press Release from Change NY. Argues against raising taxes, claiming New Yorkers are already over taxed. Announces plan to undertake a large direct mail effort.